2023
DOI: 10.5688/ajpe8917
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Suicide Prevention Training Programs for Pharmacists and Student Pharmacists

Abstract: Objective. This scoping review updates a 2018 review of suicide prevention (SP) training programs for community and student pharmacists. Five scholarly databases were searched for articles published between January 2018 and December 2020. Articles were excluded if they: 1) did not describe an educational or training program for pharmacists or student pharmacists; 2) did not explicitly include suicide; 3) focused solely on attitudes; or 4) did not provide sufficient detail to evaluate program content. The quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Although the effect of training was sustained over three to six months [ 40 ], little is known about the long-term influence on pharmacists’ attitudes, experiences, or their management of at-risk individuals. This matches the findings of another scoping review that explored suicide prevention training programmes given to pharmacists, which noted that additional research is needed to evaluate the impact of training on pharmacists’ self-efficacy and communication skills [ 45 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the effect of training was sustained over three to six months [ 40 ], little is known about the long-term influence on pharmacists’ attitudes, experiences, or their management of at-risk individuals. This matches the findings of another scoping review that explored suicide prevention training programmes given to pharmacists, which noted that additional research is needed to evaluate the impact of training on pharmacists’ self-efficacy and communication skills [ 45 ].…”
Section: Discussionsupporting
confidence: 76%
“…In order to increase pharmacists’ willingness to participate in suicide prevention and to improve their attitudes and experiences in this field, offering a proper training program is suggested. Training programs should address culture barriers and incorporate the following: role of medications in suicide [ 45 ], minimizing stigma [ 26 ], overcoming barriers, and improving knowledge and communication [ 37 ]. The 20 min, Veterans Administration (VA’s) S.A.V.E.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there are a number of suicide prevention trainings available for both pharmacy professionals and student pharmacists. 7,8 Many of these trainings are free and can be completed in less than 2 hours. Although asking someone who exhibits warning signs whether they are "talking about suicide" can feel uncomfortable, remember that asking shows the person that you care about them and want to help.…”
Section: What We Can Do As Individualsmentioning
confidence: 99%
“…Pharmacists have general psychiatry dispensing competencies, but a recent review found that whilst there has been an increase in suicide training resources for pharmacy professionals, this is not ubiquitous and may not be tailored to cultural contexts. 15 …”
Section: Introductionmentioning
confidence: 99%